2010
DOI: 10.1128/mcb.00614-09
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Roles of the Origin Recognition Complex in the Architecture and Function of Silenced Chromatin in Saccharomyces cerevisiae

Abstract: The silenced chromatin at the cryptic mating-type loci (HML and HMR) of Saccharomyces cerevisiae requires a cell cycle event between early S phase and G 2 /M phase to achieve repression. Although DNA replication per se is not essential for silencing, mutations in many of the proteins involved in DNA replication affect silencing. Each of the four silencers, which flank the silenced loci, includes an origin recognition complex (ORC) binding site (ACS). ORC directly interacted with Sir1 and recruits Sir1 to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…For example, the second histone-binding domain in the C terminus of Sir3 (20) or the modification of the ATPase domain to bind the Sir2 product O-acetyl-ADP ribose (54) could have arisen after duplication. It is also possible that even after subfunctionalization, Orc1 retained some ability to propagate along chromatin, as recently suggested (55).…”
Section: Discussionmentioning
confidence: 80%
“…For example, the second histone-binding domain in the C terminus of Sir3 (20) or the modification of the ATPase domain to bind the Sir2 product O-acetyl-ADP ribose (54) could have arisen after duplication. It is also possible that even after subfunctionalization, Orc1 retained some ability to propagate along chromatin, as recently suggested (55).…”
Section: Discussionmentioning
confidence: 80%
“…RNA analysis was performed exactly as described (51). cDNA was analyzed by quantitative PCR as described in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Here the experimental record has been equivocal. Some studies have found Sir1 limited to silencers (Zhang et al 2002), whereas others have found the protein and ORC subunits distributed throughout the HM loci (Gardner and Fox 2001;Rusche et al 2002;Ozaydin and Rine 2010). Whether Sir1 and ORC function throughout silent chromatin domains or whether they simply hitchhike onto silent chromatin as passengers of Sir4 is not yet clear.…”
Section: Sir1mentioning
confidence: 96%